Granule Protein Processing and Regulated Secretion in Neutrophils - Sheshachalam, Avinash; Srivastava, Nutan; Mitchell, Troy; Lacy, Paige; Eitzen, Gary (Frontiers in Immunology, 2014)
Neutrophils are part of a family of granulocytes that, together with eosinophils and basophils, play an essential role in innate immunity. Neutrophils are the most abundant circulating leukocytes and are vital for rapid immune responses, being recruited to sites of injury or infection within minutes, where they can act as specialized phagocytic cells. However, another prominent function of neutrophils is the release of pro-inflammatory compounds, including cytokines, chemokines and digestive enzymes, which are stored in intracellular compartments and released through regulated exocytosis. Hence, an important feature that contributes to rapid immune responses is capacity of neutrophils to synthesize and store pre-formed pro-inflammatory mediators in specialized intracellular vesicles and thus no new synthesis is required. This review will focus on advancement in three topics relevant to neutrophil secretion. First we will examine what is known about basal level pro-inflammatory mediator synthesis, trafficking and storage in secretory compartments. Second, we will review recent advancements in the mechanisms that control vesicle mobilization and the release of pre-formed mediators. Third, we will examine the upregulation and de novo synthesis of pro-inflammatory mediators by neutrophils engaged at sites of infection.